The Impact of Technology Improvement on Indonesia Manufacturing Industry Productivity - Prabowo, Prayudi Setiawan; Restikasari, Wenny; Othman, Norashida; Hutabarat, Ruth Eviana; Wasil, Mohammad (IKIP Widya Darma Surabaya, 2024)
Objective: The technology is main component in innovation, especially on industry manufacturing to increases production capability. The aim of this study is to examine the total factor productivity growth (TFPg) and its component in Indonesian industry manufacturing based on technology improvement. Method: The stochastic frontier analyses are used to calculate (TFPg). This study attempts to analyses the variation in the TFPg across year, and technology adaption. Results: The first is the analysis of year-wise comparison, show that experiences negative TFP growth or the average TFP score of current period degrades down from average score in the prior period. Second is the analysis based on technology adaption, show that the degression of productivities are mainly driven by technological regress indicating that the majority firms need innovation in technology utilized in the production process. The medium-high technology on industry manufacturing has highest score of TFP, means technology improvement support on firm productivity. Novelty: The lack of analysis regarding TFPg using a technology adaptation approach makes it a challenge to dig deeper.